Gaya Komunikasi Kepala Desa Darmasari Periode 2018-2024 Dalam Mendapatkan Simpati Masyarakat - Khusnul Abror; Daeng Sani Ferdiansyah; Tuti Handayani (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
The purpose of this study was to determine the communication style and the supporting and inhibiting factors of the communication style of the Darmasari Village Head for the 2018-2024 period in gaining public sympathy. As for the type of research used in this study is qualitative with a communication approach. The data collecation technique used in this research is by means of interviews, observation, and documentation. Then the data analysis technique used in this research is by means of data analysis, data reduction, data presentation, and drawing conclusions. While the data validity techniques used in this study were construct validity, internal validity, external validity, and constancy. The results of the research obtained are the communication style used by the village head in getting the sympathy of the community, namely the equalitarian style, relinguishing style, and the struqturing style. While the supporting factors for the head of the Darmasari Village Head in getting the sympathy of the community, namely the presence of outhority and relationship factors. Then the factors that hinderthe village head in getting the sympathy of the community, namely the level of community understanding and emotional factors.